Peran Problem Based Learning dalam Meningkatkan Keterampilan Abad 21 pada Pembelajaran Sejarah: Systematic Literature Review - Shifa Nurria; Sarah Widya Astuti; Mukhlisin Nata Hudin; Syarifuddin Syarifuddin; Rani Oktapiani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
21st-century skills are a crucial aspect that students must master, equipping them to face the challenges of modern development. In history learning, the use of Problem-Based Learning (PBL) is considered a powerful tool for transforming learning from rote memorization to active, problem-solving-based learning. This study aims to analyze the role of PBL in enhancing 21st-century skills in history learning through the Problem-Based Learning (SLR) approach. The research method used in this study is the SLR with a prism procedure. The data were obtained from a search of scientific articles through Google Scholar using the keywords Problem-Based Learning, 21st-Century Skills, and history learning. From the initial 2,540 articles obtained, after screening based on relevance, quality, and year range, six key articles were obtained. The study results indicate that PBL is effective in enhancing 21st-century skills through discussions, historical source analysis, and contextual problem-solving. This approach is considered appropriate for the curriculum because it encourages student-centered learning, rather than teacher-centered learning. Although PBL still faces several challenges in its implementation, it remains a relevant and effective learning strategy for developing 21st-century skills.